APPLICATION OF THE BUSINESS ENTITY CONCEPT TO THE FINANCIAL STATEMENTS OF SMES (International Journal of Innovative Technologies in Economy, 2024)
The financial statements must be provided according to financial accounting standards. The basic of financial accounting standards are accounting concepts. One of the concepts are business entity, i.e. the financial of business must separate from the financial of owner. The financial statements also must produce accurate and relevant information. One of the obstacles faced by many, especially MSMEs, is that they have become accustomed to using simple financial statements and it is difficult to adapt to good financial statements in accordance with the concept of business entity. The concept of business entity requires that the recording of company transactions is separate from the recording of owner transactions (Dermawan et al., 2020). The research was conducted using interviews and filling out pretest and posttest to find out whether the concept of business entity had been applied to the financial statements made and measure residents' understanding of the material presented. The results of the study show that the concept of business entity has been implemented but not fully because there are still obstacles experienced.